STRATEGI PEMERINTAH PROVINSI RIAU DALAM MENINGKATKAN INVESTASI ASING SINGAPURA - Revina, Azyzi Syahren; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The province of Riau occupies a strategic position in the national and regional investment map, particularly with the significant contribution of foreign investment from Singapore. The background to this research stems from the importance of understanding local government strategies in managing and attracting foreign investment to promote sustainable and inclusive economic growth. This study aims to analyse the Riau Provincial Government's strategies for increasing foreign investment, focusing on the role of regulation, promotion of regional potential, simplification of licensing, and infrastructure strengthening. This study uses a theoretical framework of strategy and foreign investment as its analytical tool. In this context, strategy refers to a series of policies, programmes, and concrete steps taken by the Riau Provincial Government to attract and increase foreign investment, particularly from Singapore. The method used is a qualitative approach through document studies, in-depth interviews with relevant officials, and observation of investment policy practices in Riau. The results of the study show that simplifying licensing through the OSS system, mapping regional potential, and developing integrated industrial estates are key to attracting foreign investors, particularly from Singapore. Another important finding is the need for more synergistic coordination between the central and regional governments, as well as adequate institutional support in facilitating investment. This study concludes that the success of investment strategies in Riau is highly dependent on the effective implementation of policies, the strengthening of local capacity, and the sustainability of commitments to creating a competitive and competitive investment climate. Keywords: Government Strategy, Foreign Investment, Investment, Riau Province, Singapore.